The Present's Uniqueness. (2nd February 2021) - Dolev, Yuval
Abstract: This paper offers an account of what makes the present unique. The present, it is argued, plays a constitutive role regarding succession, pastness and futurity, and is thus a pivot sustaining temporality. This is first shown with respect to experienced temporality, but the claim is then expanded to objective temporal relations and properties. A bulk of the argumentative effort goes towards establishing that, despite the crucial role experienced temporality plays in it, the result of the study is a Wittgensteinean kind of realism regarding objective time. That sets the proposal of this paper apart from both eternalism and presentism.